Commercial Driver Medical Examinations. Issue 6 (June 2015) - Thiese, Matthew S.; Moffitt, Gary; Hanowski, Richard J.; Kales, Stefanos N.; Porter, Richard J.; Hegmann, Kurt T.
<x xml:space="preserve">Abstract</x> Objective: The objective of this study was to assess relationships between body mass index (BMI) and comorbid conditions within a large sample of truck drivers. Methods: Commercial driver medical examination data from 88, 246 commercial drivers between 2005 and 2012 were analyzed for associations between BMI, medical disorders, and driver certification. Results: Most drivers were obese (53.3%, BMI >30.0 kg/m2) and morbidly obese (26.6%, BMI >35.0 kg/m2), higher than prior reports. Obese drivers were less likely to be certified for 2 years and more likely to report heart disease, hypertension, diabetes mellitus, nervous disorders, sleep disorders, and chronic low back pain (all P < 0.0001). There are relationships between multiple potentially disqualifying conditions and increasing obesity (P < 0.0001). Morbid obesity prevalence increased 8.9% and prevalence of three or more multiple conditions increased fourfold between 2005 and 2012. Conclusions: Obesity is related to multiple medical factors as well as increasing numbers of conditions that limit driving certification.